Analisis Integrasi Harga Cabai Rawit Pada Pasar Tradisional Di Kabupaten Gorontalo - Harun, Megawaty; Indriani, Ria; Boekoesoe, Yuriko (AGRI-SOSIOEKONOMI, 2023)
This study aims: 1) How is the price fluctuation of cayenne pepper in Mootilango District and the market in Limboto District, Gorontalo Regency, 2) How is integration in Mootilango District and Limboto District, Gorontalo Regency. This research was conducted at the Mootilango market and Limboto market in September-November 2022. The research method was survey or interview, sampling using purposive sampling. The sample in this study was retail traders who know the weekly price of cayenne pepper in each market based on the availability of chili price data. raw materials per week for the past year (2021 to 2022). Types of research data sources are primary data and secondary data. Analysis of the data used to determine price fluctuations of cayenne pepper in the Mootilango sub-district market and Limboto market uses the coefficient of variation method. To evaluate whether there is vertical market integration, the (IMC) method is used between the reference market and the retail market. The results showed that the Mootilango market fluctuated more than the Limboto market. The results of the IMC analysis show that the integration between the Mootilango market and the Limboto market is high. This means that price formation in the Limboto market is perfectly transmitted to the Mootilango market.